114 Pre-Alert Calls for Primary Percutaneous Coronary Intervention: A Single Centre Experience. (6th June 2015) - Rossington, Jennifer; Zaidy, Yasmin; Cole, Stephen; Cunnington, Michael; Oliver, Richard; Constanza, Pierluigi; Raza, Ali; Ali, Ali
Abstract : Introduction: Our centre operates a 24/7 primary PCI (PPCI) service delivering coronary reperfusion to a population of 1.2 million, accessed via a centralised pre-alert call system managed by coronary care nurses. Our aim was to audit PPCI pre-alerts and patient discharge diagnoses to assess the appropriateness of referrals and ensure that referrals are being correctly accepted/declined. Methods: All pre-alert calls received in 2013 were recorded on a standardised proforma and included in the study. Discharge diagnosis was retrieved from hospital case records, both locally and at district hospitals. In 52 cases this information was not recoverable. Results: 1343 pre-alert calls were received, 1227 (91%) were received directly from paramedics. The mean age was 68 ± 15 years. 586 (44%) of referrals were accepted for PPCI. 701 (52%) of the referrals had chest pain and satisfied ECG criteria (ST elevation/LBBB). 137 (10%) had neither chest pain nor met ECG criteria. 508 patients had a diagnosis of STEMI at discharge and 454 were accepted directly. 54 cases with a final diagnosis of STEMI were initially declined: 14 in cardiac arrest were directed to their local ED as policy; 18 had documented clinical reasons for declining; 7 did not meet criteria. 15 patients (3%) with chest pain and ECG criteria were declined without a documented reason; 3 were subsequently accepted after assessment at a local hospital. Of those accepted by the pre-alert pathway: 454 (77%) were discharged with a diagnosis of STEMI; 86 (15%) had an alternative cardiac diagnosis; and 46 (8%) had a non-cardiac diagnosis. LBBB accounted for 258 pre-alert calls. Of these, 29 (12%) were accepted for PPCI but only 3 had a discharge diagnosis of STEMI: 2 received PCI but did not have an acute coronary occlusion at angiography, and 1 incorrectly labelled as LBBB. 372 patients referred were aged >80 years, of which 119 (32%) had LBBB on ECG. 89 (24%) of patients aged >80 years were accepted for PPCI, compared to 497 (52%) of <80 years. 21% of patients >80 years had a final diagnosis of STEMI but were declined from the pre-alert pathway, compared to 5% of patients <80 years. 430 of referrals were female. 167 (39%) were accepted for PPCI, compared to 417 (49%) of males. 50% of those declined and subsequently discharged with STEMI diagnosis were female, which is disproportionate compared to the referral numbers. Conclusion: Patients are frequently referred who do not meet symptom/ECG criteria; however the pre-alert system correctly identifies the majority of appropriate STEMI patients without burdening the service with non-cardiac patients. Females and patients aged >80 years are more likely to be declined for PPCI due to atypical presentation and co-morbidity. Regular audit of pre-alert services is mandatory to ensure delivery of timely and appropriate PPCI in the management of STEMI.